1996
DOI: 10.1097/00004836-199606000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Brush Cytology: A Reliable Method to Detect Helicobacter pylori

Abstract: This study was conducted to verify the reliability of brush cytology in detecting Helicobacter pylori in an unselected group of patients with duodenal ulcer (DU) and nonulcer dyspepsia (NUD). Endoscopy was performed on 416 consecutive patients: group A, 94 with active DU; group B, 176 patients with DU after omeprazole (n = 78), ranitidine (n = 43), or triple anti-H. pylori therapy (n = 55); and group C, 146 patients with NUD. During endoscopy, the gastric mucosa was brushed and two biopsy samples from the antr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…Contrary to what has been stated in the literature, BC missed H. pylori in eight of our cases, in which histology identified the organisms. MGG stain was satisfactory for detecting the organism and had no additional advantage.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to what has been stated in the literature, BC missed H. pylori in eight of our cases, in which histology identified the organisms. MGG stain was satisfactory for detecting the organism and had no additional advantage.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies have shown the diagnostic accuracy of BC to range from 68% to 97.1% . The majority of the studies on BC have stressed its role in the diagnosis of malignant lesions, whereas only a few have dealt with non‐neoplastic lesions, most of them being cases of Helicobacter pylori (H. pylori) gastritis . BC is said to be particularly useful in stenosing lesions, the lesions with a bleeding tendency, flat lesions, or when there is a need for selective sampling from a larger area …”
Section: Introductionmentioning
confidence: 99%
“…Brush cytology: a sensitivity of 98% and specificity of 96% have been reported 10 . It is suggested and found to be more sensitive in some studies in comparison to biopsy histology [11][12][13] . Bacterial culture and sensitivity testing, String test 14 , Brushing urease test 15 .…”
mentioning
confidence: 99%